Manajemen Kasus Pemenuhan Kebutuhan Oksigenasi pada Pasien Tuberkulosis Paru - Muhaimin Saranani; Dian Yuniar Syanti Rahayu; Ketrin Ketrin (Health Information : Jurnal Penelitian, 2019)
Pulmonary tuberculosis is an infectious disease that attacks the lung parenchyma, caused by Mycobacterium tuberculosis (Somantri, 2009). In 2017 in Southeast Sulawesi, 2,587 new cases of BTA (+) were found. In 2016 in Kendari City Hospital, 229 cases of pulmonary tuberculosis were obtained, while in 2017 there were 286 cases (Medical Records and SIRS of Kendari City). Objective: Carry out nursing care for pulmonary tuberculosis patients in fulfilling oxygenation needs in the Lavender Room at the Kendari City Hospital. Methods: In this study, researchers used a descriptive study, namely a case study. Result: Nursing diagnosis, namely ineffective airway clearance associated with excessive mucus. After 3x24 hours of action, the results showed: the patient did not experience shortness of breath, breathing 20 times / minute, no additional breath sounds and the patient was able to cough effectively without the help of the nurse's instructions. Bottom Line: An effective cough action can help drain secretions and reduce chest pain.